Study the Structural, Dynamical, Electronic, and Magnetic Properties of CoSb3 Skutterudite Material: First-Principles Approach - Yadhav, Sukrit Kumar; Devkota, Arun; Paudel, Ganesh; Rijal, Om Shree; Neupane, Hari Krishna; Parajuli, Rajendra (Amrit Research Journal, 2025)
Skutterudite compounds have potential applications in optoelectronic, thermoelectric, and spintronic devices. In this work, we have explored the physical properties of the CoSb3 skutterudite compound using the density functional theory (DFT) method with the GGA: PBE+U functional implemented in the VASP computational package. The structural properties of CoSb3 have been investigated by optimizing its lattice parameters and bond lengths, as well as estimating its formation and cohesive energies. The results indicate that the compound is structurally stable. The dynamical properties of CoSb3 were analyzed based on the obtained phonon dispersion curves. The absence of negative frequency modes at all high-symmetry points confirms that the material is dynamically stable. The electronic and magnetic properties were determined through the analysis of the band structure, density of states (DOS), and partial density of states (PDOS) plots. From the band structure and DOS results, CoSb3 exhibits metallic behavior, as band states are observed around the Fermi energy level. For the magnetic properties, the DOS and PDOS analyses reveal that the compound possesses a finite magnetic moment, indicating that CoSb3 is magnetic in nature. The observed magnetic moment arises from the dominant distribution of down-spin electronic states in the atomic orbitals of the constituent elements.